Development and validation of computer induced distress and factors influencing technostress among ICT users - Ajibola Abdulrahamon Ishola; Chinwuche Chisom Obasi; Olugbenga Joseph Oluwole (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
The increased use of information computer technology (ICT) across the Nigerian workplace have engendered the high incident of Techno stress or Computer Induced Distress (CID) in the work space. However, proper conceptualization and measurement of this phenomenon have not been done in the Nigerian context based on the review literature. This study develops and investigate the incidence of CID, and influence of expertise and education on CID among ICT users in organisations. The study is a cross sectional survey research design. Three hundred and ninty-eighty (398) employees working in ICT related activities were selected from private and public organisations in Lagos metropolis. Results revealed a reliability and validity coefficients (Cronbach alpha. 0.91). Factorial validity yielded three factors; psychological, depression, and physiological strain dimensions. Psychological, depression, and physiological dimensions converged with CID and discriminated by level of computer related skills. CID was associated with use of lower order computers, and non-provision of ergonomic comfortable work station. There was significant effect of level of ICT skills on CID. Provision of conducive and comfortable work environment as preventive measure in reducing technostress was advised.